Autogestão - dos movimentos sociais dos trabalhadores aos movimentos dos educadores um olhar sobre o Rio Grande do Sul - Zientarski, Clarice (2006)
The present work whose subject is Self management: of the Social Movements of the Workers to the Movements of the Educators , it has as objective generality to establish relations between the autogestionários social movements and the autogestionários movements in the education and, in this proposal, it looks for to identify and to characterize the autogestionários social movements that the Europe and in Brazil of century XIX in ahead had also happened in, with special approach to that had occurred in Brazil of the end of the decade of 1970 years 1980, considering the social political and economic context of the time. In this optics if it establishes the methodology of the present work that has as base the qualitative research for what if valley of a theoretical boarding that has in history its bedding, to establish the relations necessary between the facts and power to understand them and the empirical research carried through in the educative institutions and unions on the movements carried through for the professors, either during the strikes, either in the autogestionárias proposals, detaching the cited historical period. A boarding of social and autogestionários movements implies in understanding the joint dialectic of the society politics with the civil society and its contradictions. To understand a society, or autogestionária institution is necessary to question the centralism, the bureaucracy and the hierarquização that the capitalist society has characterized in which we are inserted. It matters, therefore, an analysis of what if it configures as autogestionária society, for what if establishes relations between hierarquizada society bureaucratically and, what is reflected in pertaining to school management e, of course, in practical the pedagogical one. This demands the effort to present the facts and to interpret them in a perspective dialectic where the knowledge concrete of the reality is a process of concretion that proceeds from all for the parts and the parts for all, of the phenomena for the essence and the essence for the phenomena, the totality for the contradictions and the contradictions for the totality.